"Take a look at this!". Video annotation as a means to foster evidence-based and reflective external and self-given feedback: A preliminary study in operati on room technician training. (March 2020) - Cattaneo, Alberto A.P.; Boldrini, Elena; Lubinu, Francesco
Abstract: Receiving and giving oneself formative feedback is essential to professionals' development of reflective attitudes towards their practices. In the healthcare professions, debriefing sessions are often used to provide feedback. Such sessions often incorporate videos to support the debriefing process. However, this usually occurs with reference to simulations and not to actual practice; furthermore, the potential of using video-annotation software to analyse practice has not been fully exploited in nursing education. To explore this still under-investigated potential, the current pilot study was conducted in the domain of operation room technicians to investigate whether the use of videos of actual practice and video-annotation software affected the quality of feedback given during the debriefing sessions. The pilot experience seems to confirm that this approach is feasible in actual practice. More particularly, the results suggest that video support enables more supportive feedback about work processes and more evidence- and situation-based feedback than regular debriefing without video. The use of video annotation also tends to support more student-driven and dialogical feedback as well as tending to increase student acceptance of feedback. Additional research is needed to further investigate the feasibility of this approach within hospitals. Highlights: Video-recording operating room technicians during real practice is feasible. Video-annotation to support formative feedback is feasible. Video support enables process-oriented and evidence-based feedback. Video-annotation tends to support student-driven and dialogical feedback. Video-annotation tends to increase the student's acceptance of feedback.